2021
DOI: 10.1016/j.ejca.2021.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, safety and factors associated with disease progression in patients with unresectable (stage III) or distant metastatic (stage IV) BRAF V600-mutant melanoma: An open label, non-randomized, phase IIIb study of trametinib in combination with dabrafenib

Abstract: Background: BRAF and MEK inhibitors combination, including dabrafenib (D) and trametinib (T) have transformed the treatment of BRAF V600-mutant advanced melanoma patients, including patients with brain metastasis (BM). In a large phase IIIb, singlearm, open-label, multicenter French study, we assessed safety, response to treatment, progression-free survival (PFS) and factors associated with progression, and stratified the population into risk groups. Methods: Patients with unresectable, advanced, BRAF V600-mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…In the first step, patients were divided into two subgroups according to the largest difference in PFS. In the next step, the process was repeated until either subgroup included at least 10% of all treated patients or no additional splitting was possible 19 . Internal validation was performed by bootstrapping in R (The R Foundation for Statistical Computing, Vienna, Austria) using 2000 resamplings 20 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first step, patients were divided into two subgroups according to the largest difference in PFS. In the next step, the process was repeated until either subgroup included at least 10% of all treated patients or no additional splitting was possible 19 . Internal validation was performed by bootstrapping in R (The R Foundation for Statistical Computing, Vienna, Austria) using 2000 resamplings 20 .…”
Section: Methodsmentioning
confidence: 99%
“…In the next step, the process was repeated until either subgroup included at least 10% of all treated patients or no additional splitting was possible. 19 Internal validation was performed by bootstrapping in R (The R Foundation for Statistical Computing, Vienna, Austria) using 2000 resamplings. 20 Statistical analyses were performed using GraphPad Prism 9 software, R, and EZR (Saitama Medical Center, Jichi Medical University) 21…”
Section: Statistical Analysesmentioning
confidence: 99%
“…When assessing the efficacy of dabrafenib and trametinib for treating 125 cases of BRAFmutant melanoma, results from the phase-2 COMBI-MB trial revealed a shorter median progression-free survival (4.2-7.2 months) and duration of clinical response (4.5-8.3 months) for patients with brain metastasis as opposed to those in patients without brain metastasis. 4,8) However, this trial did not report the potential differences between melanotic and amelanotic melanomas. Furthermore, the correct interpretation of results from this trial was complicated by the occurrence of toxic side effects, which led to the interruption of treatment in 50% of the patients and discontinuation in 10% of the patients.…”
Section: Introductionmentioning
confidence: 96%
“…3) Thus, there is a need for the development of better treatments for the improvement of outcomes in patients with brain metastasis caused by melanoma. 4) Although both primary and metastatic melanoma generally display black coloration, reflecting the presence of melanin pigment, lack of pigmentation as a primary morphological feature cannot be exploited to completely rule NMC Case Report Journal Vol. 10,2023 out the presence of melanoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation